SUSTAINABLE INFRASTRUCTURE DEVELOPMENT PROBLEMS IN CENTRAL ASIA - Baizakova, K.; Kukeyeva, F. (Farabi Journal of Social Sciences, 2018)
This article is devoted to the 9th goal of the POST 2015 Programme – creation of resilient infrastructure, facilitation of inclusive and sustainable industrialization and foster innovation. The condition and development level of transport infrastructure is an essential factor in formation and acceleration of sustainable development of regions and their effective cooperation. Issues of resilient infrastructure development bear peculiar traits in Central Asia region, because they are in need of overcoming geographic isolation, solving the problem of being inaccessible and dependent on countries, which provide them an avenues to world markets. Successful solution of infrastructure issues gives Central Asia states opportunities to diversify the resources of state revenues, create new sectors of economy and reduce dependence on raw materials export. As for the Kazakhstani government, it prioritizes promotion of competitiveness on the global market of services, and correspondingly, stimulation of trade flows growth through its territory. Keywords: Central Asia, infrastructure, railway, highway, transport corridors, TRACECA.